Pengaruh Pelatihan dan Pengembangan Karyawan terhadap Produktivitas Kerja Karyawan Pada CV Firjhi Karya Group - Lia Indah Safitri (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of training and development on employee work productivity at CV FIRJHI KARYA GROUP East Jakarta, both partially and simultaneously. This research uses a quantitative approach with associative methods. Data collection techniques use observation, questionnaires and literature study. The number of samples in this study was 30 respondents and the data was processed using the SPSS.21 application. Results Research shows that training has a partial positive effect and significant to employee work productivity, as evidenced by the T Test obtained from The calculated t value is 4.544 > greater than the t table 2.051 and the significance value is 0.000 < smaller than 0.05. And partial development has a positive effect significant impact on employee work productivity, as evidenced by the T Test results obtained from The calculated t value is 6.582 > greater than the t table 2.051 and the significance value is 0.001 < smaller than 0.05. Then Training and Development simultaneously have a positive and significant effect on employee work productivity. This is proven based on the F Test results obtained from the calculated f value of 103.510 > greater than f table 3.34 and a significance value of 0.000 < smaller than 0.05.